2021
DOI: 10.1109/access.2021.3056724
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network Utilizing Error-Correcting Output Codes Support Vector Machine for Classification of Non-Severe Traumatic Brain Injury From Electroencephalogram Signal

Abstract: A sudden blow or jolt to the human brain called traumatic brain injury (TBI) is one of the most common injuries recorded in the health insurance claim. Generally, computed tomography (CT) or magnetic resonance imaging (MRI) is required to identify the trauma's severity. Unfortunately, CT and MRI equipment are bulky, expensive, and not always available, limiting their use in TBI detection. Therefore, as an alternative, this study presents a novel classification architecture that can classify non-severe TBI pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Enschede, Netherlands) at a sampling rate of 1000 Hz. The WaveGuard TM Original EEG head cap with gel-based electrodes was employed according to the international layout of 10-10 electrode system for electrode placement [69], as shown in Figure 2.…”
Section: ) Eeg Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Enschede, Netherlands) at a sampling rate of 1000 Hz. The WaveGuard TM Original EEG head cap with gel-based electrodes was employed according to the international layout of 10-10 electrode system for electrode placement [69], as shown in Figure 2.…”
Section: ) Eeg Proceduresmentioning
confidence: 99%
“…Data pre-processing was carried out using the EEGLAB v2019.0, an open source software [71] running on MATLAB (Mathworks Inc. R2020a) with the custom MATLAB code. In the first step, the power line noise was removed by applying a notch filter at 50 Hz (in Malaysia) [69] with the pop_eegfiltnew () function of EEGLAB to the signal r. The resting-state EEG recording with eyes-closed aided in the reduction of rapid eye movement (i.e., blinking and visual fatigue) [72]. Next, a small number of blink-like signal shapes and muscular activity were manually selected and removed [29].…”
Section: ) Eeg Data Filtering and Artifact Removalmentioning
confidence: 99%
“…SVM is a mathematically based algorithm for creating a model for data analysis. The SVM algorithm is rapidly used in machine learning studies for better classification [40][41][42]. J.48 Algorithm.…”
Section: Data Preparationmentioning
confidence: 99%
“…ECOC ensemble has been proposed in many areas to improve the classification performance. For example, in [15], it was shown that 99.7% recognition can be achieved using CNN-ECOC for the case of brain tumor detection. Similarly, for skin cancer detection [16], AlexNet, a pre-trained CNN model, was used to extract the features.…”
Section: B Motivationmentioning
confidence: 99%